Understanding the mechanisms in accelerated drug reactions. Issue 4 (August 2016) - Torres, María J.; Salas, Maria; Ariza, Adriana; Fernández, Tahia D.
Abstract : Purpose of review: The purpose is to understand the underlying mechanisms of accelerated allergic reactions to drugs, defined here as reactions occurring between 1 and 24 h after drug intake. Recent findings: Recent publications have shown that accelerated reactions are T cell-mediated, although an IgE mechanism cannot be ruled out in some cases. Summary: Classification of allergic reactions to drugs is complex. Based on the time interval between drug administration and appearance of the clinical reaction, as well as the type of clinical symptoms, they can be classified as: immediate, typically appearing from less than 1 to 6 h after the last drug administration and nonimmediate, occurring at any time from 1 h after drug administration. Therefore, overlap exists in what the Levine classification defined as accelerated reactions, where clinical symptoms are mainly urticaria and less often exanthema and serum sickness-like reactions. The immunological mechanisms involved suggest that they are T cell-mediated reactions with a Th1 pattern, comprising increased production of IFNγ, TNFα, the chemokine CXCL9 and its corresponding receptor CXCR3. In most cases an IgE-mediated response is ruled out because of negative immediate skin test results, no detection of serum-specific IgE antibodies or tryptase, and no skin-secreted tryptase. However, an IgE-mediated response can be demonstrated in exceptional situations. Finally, serum sickness-like reactions have been reported as an immune complex-mediated accelerated reaction. However, the exact mechanism has not been confirmed.